Generation mean analysis of resistance to white rust in Indian mustard (Journal of Oilseed Brassica, 2026)
White rust is an economically important disease of oilseed Brassicas and generation mean analysis of three crosses was done to study the nature and magnitude of gene action governing resistance to this disease. Simple additive(d)- dominance(h) model could not explain the genetics of white rust resistance suggesting the presence of non-allelic gene interaction. The estimates of additive × additive (i), additive × dominance (j) and dominance × dominance (l) gene effects were significant for the crosses Varuna × BioYSR and Kranti × Heera, however barring additive × dominance (j) gene effect, all other gene effects were significant for the cross RH 749 × BioYSR. The magnitude of non-fixable gene effect (h+l) was greater than fixable gene effect (d+i) for all the crosses. The opposite sign of h and l suggested presence of duplicate gene action for white rust resistance in all the crosses. The magnitude of broad sense heritability was high in all the crosses with desirable mid-parent heterosis.